2013
DOI: 10.3390/nu5114503
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dairy Proteins as Technological and Nutritional Improvers of Calcium-Supplemented Gluten-Free Bread

Abstract: Effect of dairy proteins on gluten-free dough behavior, and nutritional and technological properties of gluten-free bread was evaluated. Experimental doughs, containing dairy powders, showed low consistency. Obtained gluten-free breads were rich in proteins, and, regarding the energy value delivered by proteins, they could be considered as a source of proteins or high in proteins. Applied dairy proteins affected the technological properties of experimental breads causing a significant (p < 0.05) increase of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 43 publications
4
32
1
5
Order By: Relevance
“…There are also breads composed of milk proteins (3%) or skimmed milk (3%). Dairy proteins have been extensively studied and are known to be effective for enhancing Maillard reactions, improving the color of the loaves, even at small doses (Gallagher, Gormley, & Arendt, 2003;Krupa-Kozak, Baczek, & Rosell, 2013). Nonetheless, the fact that many manufacturers offer products free of gluten and lactose or dairy products (because a certain intolerance to lactose may be associated with celiac disease; Ojetti et al, 2005) likely influenced the lower use of milk proteins.…”
Section: Ingredientsmentioning
confidence: 99%
“…There are also breads composed of milk proteins (3%) or skimmed milk (3%). Dairy proteins have been extensively studied and are known to be effective for enhancing Maillard reactions, improving the color of the loaves, even at small doses (Gallagher, Gormley, & Arendt, 2003;Krupa-Kozak, Baczek, & Rosell, 2013). Nonetheless, the fact that many manufacturers offer products free of gluten and lactose or dairy products (because a certain intolerance to lactose may be associated with celiac disease; Ojetti et al, 2005) likely influenced the lower use of milk proteins.…”
Section: Ingredientsmentioning
confidence: 99%
“…Generally, bread development without gluten has involved the use of diverse ingredients and additives with the purpose of imitating the visco‐elastic properties of the gluten and consequently to obtain bread‐like products (Table ). In recent years, there has been extensive research for the development of gluten‐free bread, involving diverse approaches, such as the use of different naturally gluten‐free flours (rice, maize, sorghum, soy, buckwheat), and starches (maize, potato, cassava, rice, bean), dairy ingredients (caseinate, skim milk powder, dry milk, whey), gums and hydrocolloids [guar and xanthan gums, alginate, carrageenan, hydroxypropyl methylcellulose (HPMC), carboxymethyl cellulose (CMC); emulsifiers (DATEM, SSL, soy lecithin], other non‐gluten proteins (milk proteins, egg proteins, legume proteins, e.g. soy bean and pea); enzymes (cyclodextrin glycosyltranferases, transglutaminase, proteases, glucose oxidase, laccase), and prebiotics (inulin), or combinations thereof; as alternatives to gluten, to improve the structure, mouthfeel, acceptability and shelf‐life of gluten‐free bakery products.…”
Section: Influence Of Gluten‐free Ingredients On Dough Rheology and Qmentioning
confidence: 99%
“…In this review, data of dough characteristics and bread quality from previously reported recipes have been compiled to understand their possible relationship (Table ). Visco‐elastic moduli, pasting properties and Mixolab parameters collected from the reported gluten‐free dough/batter properties have been pooled and correlated with specific volume and crumb texture parameters . Table displays the significant correlations found between dough parameters obtained during the heating and cooling cycles with the Mixolab and the instrumental quality parameters [specific volume and Texture Profile Analysis (TPA)–hardness].…”
Section: Influence Of Gluten‐free Ingredients On Dough Rheology and Qmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important source of amino-acids in gluten-free products are diary proteins, which positively influence nutritional value and quality of gluten-free bread. They are a good source of calcium and essential amino acids, such as lysine, methionine and tryptophan (Krupa-Kozak et al 2013). The addition of diary proteins strengthens structure, improves texture and color of bakery products and slows down its ageing.…”
Section: Research Highlightsmentioning
confidence: 99%